MENGUSUNG MODERASI ISLAM DI TENGAH MASYARAKAT MULTIKULTURAL - Darlis Dawing (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
In the context of diversity in all aspects, Indonesia is referred to as one of the mulcultural nation. The advantages it has must be maintained and addressed with full of wisdom, because multicultural society is very span with conflict. In this article, the authors answered these concerns by carrying Moderation of Islam as a solution in a multicultural society. Through the philosophical historical approach in the searching of Islamic literature and the words of the Prophet and the behavior of Companions, it can be concluded that Moderation of Islam crystallizes in all scientific discipline in Islam, starting from aspect of aqidah, shariah, tafsir, tasawuf and da'wah. The universal teachings implied from the discipline of science above are justice, equality, balance, flexibility, simplicity and tolerance in carrying out religious teachings that are derived for human benefit